2020
DOI: 10.3389/fmicb.2020.530906
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Proteocomplexome of Campylobacter jejuni Using 2-D Blue Native/SDS-PAGE Combined to Bioinformatics Analysis

Abstract: Campylobacter is the leading cause of the human bacterial foodborne infections in the developed countries. The perception cues from biotic or abiotic environments by the bacteria are often related to bacterial surface and membrane proteins that mediate the cellular response for the adaptation of Campylobacter jejuni to the environment. These proteins function rarely as a unique entity, they are often organized in functional complexes. In C. jejuni, these complexes are not fully identified and some of them rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 110 publications
(136 reference statements)
0
2
0
Order By: Relevance
“…Many of them interact with other proteins to fulfil their biological function (Carlson et al 2019 ). The membrane integrity is therefore crucial for these complexes (Sachs and Engelman 2006 , Guérin et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many of them interact with other proteins to fulfil their biological function (Carlson et al 2019 ). The membrane integrity is therefore crucial for these complexes (Sachs and Engelman 2006 , Guérin et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the meantime, individual amino acid mutations could not affect presentation of antigen and the subsequent immune response ( Lozano et al, 2021 ). Over the recent years, it is found that C. jejuni Omp18, AhpC outer membrane protein, and FlgH flagellin subunit feature numerous advantages, including but not limited to strong antigenicity, expression in varying strains, and sequence conservation ( Watson et al, 2014 ; Guérin et al, 2020 ; Quintel et al, 2020 ). Therefore, Omp18, AhpC, and FlgH could be adopted as surface protein antigens for screening dominant epitopes of C. jejuni .…”
Section: Introductionmentioning
confidence: 99%